Granulomatous Myositis Associated With Acetylcholine Receptor Antibodies Without Clinical Myasthenia. Issue 1 (September 2021) - Jin, Jingxiao; Isfort, Michael C.; Ascherman, Dana P.; Lacomis, David
Abstract : Abstract: Myasthenia gravis associated with concurrent inflammatory myopathy is a rare but well-described syndrome, most often seen in patients with thymoma. We present a case of biopsy-proven granulomatous myositis associated with positive acetylcholine receptor binding, blocking, and modulating and antistriated antibodies, without clear clinical symptoms of myasthenia gravis and in the absence of thymoma. In addition, we include rarely reported neuromuscular ultrasound findings of granulomatous myositis in a patient without sarcoidosis. Inflammatory myopathy may precede development of myasthenia gravis in myasthenia gravis associated with concurrent inflammatory myopathy, and it is important to remain vigilant for symptoms suggestive of myasthenia gravis, especially in the presence of positive myasthenia-associated antibodies.